Azolla & Soya Hulls-Substitutes for Urea in Coir Pith Composting Using Pleurotus Sajor Caju - Radhakrishnan, S.; Ravindranath, Anita Das; Sarma, U. S.; Jayakumaran, Nair A. (International Coconut Community Journal, 2011)
Bio composting process is the available means of converting various organic wastes generated from the industry and the agricultural sectors into beneficial products such as biofertilizers and as a soil conditioners. The unique feature of these agricultural wastes are their organic content, pH, and high C: N ratio. Coir pith is a biomass residue obtained during the extraction of coir fibre from coconut husk. Accumulation of coir pith leads to an environmental concern and its management is a major problem with all coir industrialists. The high quantum of its production and the difficulties experienced in its disposal have tended to create a major problem of pollution of large areas of land and water in coir fiber extraction units. Therefore, biodegradation of coir pith is an essential requirement to control pollution. Coir pith, even though a problematic waste; it is a potential wealth when it is converted into valuable organic manure by microbial degradation. A method of composting of coir pith with urea has been developed by Coir Board, India using a fungus viz., Pleurotus sajor caju commercially known as Pithplus. Application of urea releases higher concentration of ammonia in the soil making it more acidic and retards soil natural fertility. Hence an alternative cost effective nitrogen supplement needs to be developed as a substitute to urea for composting of coir pith. The present study aims at the formulation of bio organic manure from coir pith avoiding inorganic urea in the composting. Overall assessment on the physico chemical properties of the biodegraded coir pith leads to the conclusion that a combination of Azolla and Soya hulls (2:1 ratio) was found to be efficient in lignin degradation and contribute to novel changes in coir pith